Why a new representation model for games: the code form - Matos, M. C. P. (2015)
The aim of this work is to present a representation model of games which will establish the characteristics of each game with complete rigour. This model is presented emphasizing applications of theory, as much or more than the theory itself due to thinking, on the one hand, that applications help understand theory, and on the other, that applications illustrate the process of model building. Thus, this model is intended to illustrate the full rigour games both in terms of information, and in terms of real time structure of the games